APPLICATION OF CASSAVA PEEL STARCH AS A RAW MATERIAL OF EDIBLE COATING WITH ADDITION OF CHITOSAN TO EXTEND RIMAU GERGA LEBONG (RGL) ORANGE OF BENGKULU SELFLIFE - siska Apriyani; Adwini Prasetya; Sigit Mujiharjo (Jurnal Agroindustri, 2020)
Rimau Gerga Lebong (RGL) is a superior citrus fruit of Bengkulu Province, but this fruit is easy to rot, especially if stored at room temperature, so it needs technology that able to extend its shelf life to have its maximum benefit. This study aims to explain the effect of cassava peel starch concentration plus chitosan on the quality of RGL citrus fruits for 20 days of storage and determine the best concentration applied. This study used a Completely Randomized Design (CRD) with two different factors namely the concentration of cassava peel starch; 3%, 5%, and 7% and chitosan concentration; 0.0%, 0.5%, 1.0%, 1.5% with observed variables of weight loss, hardness, total dissolved solids, fruit juice levels, and vitamin C levels observed every 5 days for 20 days storage at room temperature. The research data were analyzed graphically and used ANOVA to explain the effect and significance of the treatment to determine the best one. The results showed that the use of 3-5% (w / v) cassava peel starch combined with the addition of 0.0-1.5% (w / v) chitosan to coat RGL citrus fruits stored for 20 days at room temperature was able to reduce the rate of shrinkage weight so that the value is only around 6.33-8.12%; able to maintain fruit hardness so that the value ranges from 1.3 to 1.7 kg; able to maintain total dissolved solids so that the value ranges from 10.8 to 12.6o Brix; able to maintain juice levels so that the value ranges from 53.61 to 73.00%, and is able to suppress the rate of decrease in vitamin C so that the value ranges from 1.52 to 2.38 mg / 5ml. The recommended concentration of cassava starch to be applied is 5% (w / v) with chitosan added with a concentration of 1.5% (w / v).